THE EFFECT OF IMAGE MEDIA-ASSISTED SAS METHOD ON READING AND WRITING ABILITY IN BEGINNING OF THE FIRS - Rerung, Selpi; SINRING, ABDULLAH; ZAIDIN, M. ARIFIN (PBSI, FKIP UNISSULA, Semarang, 2023)
The purpose of the research is to analyze The effect of the image media-assisted SAS method on reading and writing ability at the beginning of the first-grade students of SD Negeri 1 Sopai.This research uses a quantitative approach with a Quasi-experimental research design with a non-equivalent pretest-posttest model. The research population was all first-grade students of SD Negeri 1 Sopai, North Toraja Regency. The total population is 59 students, divided into two study groups, with each class IA being 29 students while class IB was 30 students. The sampling technique used random cluster sampling and class IA as the experimental class, while class IB was the control class. The data collection technique uses a performance test for writing and an initial reading test. Based on the comparative analysis of the average reading ability at the beginning of the experimental class and the control class, the value of t = 7.495> 1.69726 and sig. (2-tailed) = 0.00<0.05 states that the SAS method assisted by image media significantly affects the student's initial reading ability. For the students' initial writing ability, the t-value is 7.390>1.69726 and sig. (2-tailed) = 0.00<0.05, this shows that the SAS method significantly affects the writing ability of the first grader of SD Negeri 1 Sopai.